Are Temporal Artery Biopsy Findings Related to PET/CT Findings in Giant Cell Arteritis?. (28th May 2022) - Mestre-Torres, Jaume; Martínez-Valle, Fernando; Gabaldón, Alejandra; Simó-Perdigó, Marc; Salcedo-Allende, M. Teresa; Navales-Mateu, Ignacio; Solans-Laqué, Roser
Abstract : Background: Two clinical subsets of giant cell arteritis have been identified with different histological and CT findings. However, PET/CT findings have not been compared with temporal artery biopsy (TAB). Objective: The aims of this study were to describe clinical and histological findings in patients with giant cell arteritis according to the presence or absence of aortitis in PET/CT at the disease diagnosis, and to identify independent factors related to aortic involvement. Methods: Patients were included and followed prospectively. Clinical symptoms and TAB findings were recorded. PET/CT was performed in the first 10 days of steroid therapy. Aortitis was defined if a grade 3 uptake on visual analysis was present on arterial wall. Clinical and histological variables were compared according to the presence or absence of aortitis on PET/CT. Multivariate analysis was performed to identify independent factors related to the presence of aortitis. Results: Twenty-seven patients (median age, 77.6 years) were included. PET/CT was performed with a median delay of 5.0 days. Aortitis was observed in 8 patients. Patients with aortitis were younger (69.9 vs 83.7 years, P = 0.04) and had less frequently ischemic manifestations (25.0% vs 84.2%, P = 0.006) than patients without aortitis. Giant multinucleated cells were more frequent on TAB from patients with aortitis (71.4% vs 16.7%), and its presence was an independent risk factor for the occurrence of aortic involvement on PET/CT (odds ratio, 12.2; P = 0.046). Conclusions: Our study shows that giant cells on TAB are associated with the presence of aortitis on PET/CT. Patients with aortic involvement are younger and show less frequently ischemic manifestations.